Advanced Nursing Directives: Integrating Validated Clinical Scoring Systems into Nursing Care in the Pediatric Emergency Department - Erin Kate deForest; Graham Cameron Thompson (Nursing Research and Practice)
In an effort to improve the quality and flow of care provided to children presenting to the emergency department the implementation of nurse-initiated protocols is on the rise. We review the current literature on nurse-initiated protocols, validated emergency department clinical scoring systems, and the merging of the two to create Advanced Nursing Directives (ANDs). The process of developing a clinical pathway for children presenting to our pediatric emergency department (PED) with suspected appendicitis will be used to demonstrate the successful integration of validated clinical scoring systems into practice through the use of Advanced Nursing Directives. Finally, examples of 2 other Advanced Nursing Directives for common clinical PED presentations will be provided.